Clinical workflows based on OpenEHR using BPM - Ribeiro, Tiago (2019)
The integration of clinical workflows in electronic health records systems has been problematic due to the complex nature of clinical processes. For that reason, many health institutions have opted to maintain a few clinical workflows on paper, which has been compromising the quality and efficiency of several provided services. The purpose of this study is to investigate if the OpenEHR model can be applied in the configuration and management of clinical workflows using Business Process Modelling (BPM), with the focus on clinical forms based on OpenEHR archetypes and having has background the institution Centro Hospitalar do Porto (CHP). The need to review the workflows is pertinent due to the lack of integration of clinical workflows on their Electronic Health Records system. To analyse this possibility, a prototype was created containing: i) a BPM tool to configure and manage the clinical workflows; and ii) a web application to execute them and call the external clinical forms. The obtained results proved that the use of a BPM tool to configure clinical workflows allows the interoperability and flexibility of the prototype, which helps to improve the quality and efficiency of the clinical practice.